(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
The article examines approaches to improving financial reporting in the public sector through the implementation of International Public Sector Accounting Standards (IPSAS). Particular attention is paid to the role of IPSAS as a tool for increasing transparency, accountability and efficiency of public finance management. The objectives of implementing standards, such as improving the quality of financial information, attracting investment and strengthening trust in government agencies, are analyzed. The features of IPSAS adaptation in Uzbekistan are discussed, including the development of national standards, training of specialists, modernization of accounting systems and regulatory support. The challenges associated with the implementation of standards and the prospects for their application to ensure sustainable economic development are also examined